Waste sourced bio-based substances for solar-driven wastewater remediation: Photodegradation of emerging pollutants - Gomis, J. (2014)
The effect of soluble bio-based organic substances (SBO) isolated from urban wastes on photochemical wastewater treatments was investigated using a mixture of six emerging pollutants (EPs), namely acetaminophen, caffeine, acetamiprid, clofibric acid, carbamazepine and amoxicillin. Solar simulated experiments showed that although SBO were able to enhance the indirect photolysis of the EPs, they could not compensate for the light screening effect produced by these colored materials. In contrast, SBO were able to enhance photo-Fenton at slightly acidic conditions (pH = 5.2), most probably increasing iron availability. In the later case, the order of reactivity (amoxicillinPcarbamazepine Pclofibric acid > caffeine > acetaminophen > acetamiprid) was similar to that of the rate constants determined for all six EPs with OH. Finally, experiments performed at pilot plant scale with real sunlight at pH = 5.2 and SBO showed that 5 of the EPs were removed in only 25 min and only acetamiprid was more resistant to the process. The overall results show not only how we can use waste to clean out wastes, but also contribute to the studies which show how wastes can become a source of revenue through the industrial exploitation of their chemical value.